EKSTRAKSI DAN ANALISA DIETARY FIBER DARI BUAH MENGKUDU (Morinda citrifolia) - Sapta Raharja, Imam Paryanto dan Fitria Yuliani (Jurnal Teknologi Industri Pertanian, 2004)
ABSTRACTA dietary product obtained from the Indian mulberry (Morinda citrifolia) plant and the process of extracting and purifying the fiber was disclosed.  According to one embodiment, the Indian mulberry pulp was washed and separated from the juice by filtration.  The wet pulp was pasteurized.  The wet pulp can be further processed by drying to obtain dietary fiber.  This research was to compare the characteristic of dietary fiber that is producd by acid and alkali hydrolysis.  The characteristics investigated were yield, whiteness, water holding capacity, SDF, IDF, TDF, cellulose, hemi-cellulose, lignin and sollubility.  The variable of this research gave significant response to its characteristic except to hemi-cellulose content. Key word : indian mulberry, dietary fiber, acid hydrolysis, alkali hydrolysis.